2022
DOI: 10.1536/ihj.21-663
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Inter-Rater and Intra-Rater Reliability of Remote Dielectric Sensing Measurement

Abstract: Remote dielectric sensing (ReDS) is a recently introduced non-invasive electromagnetic-based device used to quantify lung fluid levels. Nevertheless, its inter-rater and intra-rater reliability remain uncertain. In 10 healthy volunteers, ReDS values were measured three times successively by the officially trained expert examiner to validate intra-rater reliability. Similar measures were performed by a total of three examiners to validate inter-rater reliability. Intra-class correlation (ICC) was applied to val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In this regard, the reproducibility of ReDS measurements becomes a crucial issue. Thankfully, a recent study by Hori et al 25 has demonstrated an almost perfect agreement between repeated ReDS measurements. Consequently, a >2% change in ReDS values should be deemed clinically meaningful and applicable in daily practice.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this regard, the reproducibility of ReDS measurements becomes a crucial issue. Thankfully, a recent study by Hori et al 25 has demonstrated an almost perfect agreement between repeated ReDS measurements. Consequently, a >2% change in ReDS values should be deemed clinically meaningful and applicable in daily practice.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, another two measurements were made right after the end of the 6MWT. One study has shown almost perfect intrarater reliability of the ReDS system, with an intraclass correlation of 0.966–0.988 25. The operator was blinded to the clinical information of the study participants.…”
Section: Methodsmentioning
confidence: 99%
“…However, almost perfect reliability could be achieved via examination by two raters. 22 Other factors are also studied that could affect the ReDS measurement. For example, it was reported that ReDS measurement should be conducted in a sitting posture.…”
Section: Reds Technologymentioning
confidence: 99%
“…While the ReDS system is acknowledged for its ability to provide reproducible information regarding lung fluid content, it is crucial to adhere to the manufacturer’s instructions when taking measurements. In a pioneer study by Hori et al 10 , the inter-rater and intra-rater reliability of ReDS measurements were examined. The results revealed a high level of intra-rater reliability, with intra-class correlation coefficients ranging from 0.966 to 0.988 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In a pioneer study by Hori et al 10 , the inter-rater and intra-rater reliability of ReDS measurements were examined. The results revealed a high level of intra-rater reliability, with intra-class correlation coefficients ranging from 0.966 to 0.988 10 . However, it is worth noting that the inter-rater reliability exhibited a lower intra-class correlation coefficient of 0.683 10 .…”
Section: Introductionmentioning
confidence: 99%